An update on mortality and morbidity in patients with very low postoperative hemoglobin levels who decline blood transfusion (CME). Issue 10 (17th February 2014) - Shander, Aryeh; Javidroozi, Mazyar; Naqvi, Sajjad; Aregbeyen, Oshuare; Çaylan, Mustafa; Demir, Selma; Juhl, Anna
Abstract : Background: Severely anemic patients for whom blood transfusion is not an option provide highly valuable information on risks of anemia and alternative management strategies. Study Design and Methods: This is a retrospective study of consecutive patients at least 18 years old who could not be transfused, had surgery at a patient blood management center between 2003 and 2012, and had at least one hemoglobin (Hb) measurement of not more than 8 g/dL during the postoperative period. The primary outcome measure was mortality, occurring anytime in the period after the surgery until discharge or 30th day after the surgery, whichever was sooner. Postoperative morbidities included the occurrence of any of sepsis, pneumonia, myocardial infarction, deep wound infection, congestive heart failure, and arrhythmia. Results: A total of 293 patients (including 288 who self‐identified as "Jehovah's Witness") were eligible and enrolled. The mean ± SD age of the patients was 61.5 ± 16.9 years and 74.1% were female. Overall mortality rate was 8.2% (95% confidence interval [CI], 5%‐11.3%). Unadjusted odds ratio (OR) of death per each 1 g/dL decrease in the nadir postoperative Hb was 2.04 (95% CI, 1.52‐2.74); OR of death after adjustment for other significant factors (urgency, American Society of Anesthesiology score, and age) was 1.82 (95% CI, 1.27‐2.59). Conclusion: Our study confirms the previously reported low risk of mortality in upper nadir Hb ranges of 7 to 8 g/dL and much higher risk in lower ranges, albeit the number of patients reaching extremely low Hb levels were lower than previous report, possibly suggestive of improved management strategy of these patients.